KAJIAN HUKUM ISLAM PADA PRAKTIK BAGI HASIL PENGOLAHAN SAWAH DENGAN SISTEM SETORAN - Firmansyah, Kholis (JURNAL HAKAM, 2024)
The scope of study of this research is "Fiqih Muamalah" in the agricultural sector, especially in terms of processing agricultural land using a deposit system, namely cooperation between land owners and farmers. The agreement stipulated is that the land owner provides the land, and the farmer prepares capital and work, from planting to harvest, and is obliged to deposit 3 quintals to the land owner. This research aims to analyze the potential income obtained by both parties, as well as analyzing the practice of processing rice fields using a deposit system from an Islamic economic law perspective, which is implemented in Jombang, East Java. This research uses a qualitative method with a case study approach. data collection through interviews with farmer group leaders, observation and documentation. The research results show that the implementation of the deposit system is that land owners hand over land to farmers for planting. Farmers prepare capital costs and work, starting from seed costs, maintenance to harvest costs, with the stipulation that farmers are obliged to deposit 3 quintals of harvest to the land owner after harvest, from land with an area of Banon 100 (1400 m2), and the remainder from the harvest becomes owned by farmers. In muamalah jurisprudence, this practice is an Ijarah contract with payments made over time. The law is permissible, as long as it does not violate sharia rules. Meanwhile, in the third planting, namely soybean planting, the contract concept used is mukhabarah. The overall profit potential in 1 period (1 year) from the practice of ijarah contracts and mukhabarah contracts is that land owners get a profit of 37.5% and farmers get a potential profit of 62.5%.